THERAPEUTIC REFUSAL AND PATIENT AUTONOMY: LIMITS BETWEEN THE RIGHT TO CHOOSE AND HEALTHCARE PROFESSIONALS’ DUTY OF CARE - Carlabianca Cabral de Jesus Canevari; Joyce Lara de Lima Mendes; Izabela Castro e Silva; Glaziélia Ferreira Franco; Ivanei Rodrigues da Silva; Angela Maria Fernandes da Silva; Thalita Sena Ribeiro Silva; Renato Canevari Dutra da Silva (Artefactum - revista de estudos interdisciplinares, 2026)
Therapeutic refusal expressed by a competent and conscious patient sits at the point of tension between the fundamental right to self-determination and the duty of care that guides the conduct of healthcare professionals. The research question guiding this article can be stated as follows: what are the legal and ethical limits that reconcile respect for patient autonomy with the healthcare professional’s duty of care when facing refusal of medical treatment, including in life-threatening situations? The article aims to critically analyze the constitutional, civil and deontological treatment of therapeutic refusal in Brazilian law, with emphasis on Supreme Federal Court case law and the discipline set by the Federal Council of Medicine. Methodologically, this is qualitative, exploratory, legal-dogmatic research, developed through a review of bioethical and legal literature and documentary analysis of legislation, professional resolutions and judicial precedents. The results show that Brazilian case law, notably in general repercussion Themes 952 and 1069 of the Supreme Federal Court, consolidated the right to therapeutic refusal grounded in religious conviction, even in life-threatening situations, while the infra-legal discipline of the Federal Council of Medicine remains challenged, under concentrated constitutional review, regarding its limits and conditions. It is concluded that the duty of care does not authorize imposing treatment against the will of a competent patient, and must instead translate, in cases of refusal, into a duty of qualified information, the offer of therapeutic alternatives and palliative care.